Chitosan derivative composite bone repair material and preparation method and application thereof
Patent Information
- Application Number
- CN202611112543.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-13
AI Technical Summary
然而,单一的羟基磷灰石由于缺乏了有机质部分,无法充分模拟细胞黏附、增殖和分化的骨细胞外基质(ECM)复杂环境,这常导致骨愈合较慢,愈合效果不佳,因此在骨修复材料中同时构建无机质和有机质两部分是十分必要的
(1)本发明的骨修复材料中的煅烧骨具有天然骨羟基磷灰石成分和多孔结构,羟基磷灰石具有骨传导、骨诱导作用,天然多孔结构为新骨形成提供稳定的三维支撑结构,也为活性金属盐提供了储藏池作用;骨修复材料中的钙、镁、锶、锌的二价金属盐均是骨生长所必须的金属盐,具有促进骨基质矿化,促进骨再生活性;骨修复材料中的羧基化-磷酸化壳聚糖,磷酸基和羧基都可以很好地与二价金属盐结合,磷酸基与二价金属离子的结合力更强,羧基与二价金属盐的结合力相对磷酸基弱,如此以大分子氨基多糖为骨架的通过其磷酸基、羧基形成了不同结合力、不同释放力的活性金属离子梯次缓释多糖;氨基多糖大分子骨架更好地模拟细胞外基质多糖结构,有利于骨髓间充质干细胞和成骨细胞的生长增殖,与羧基结合的活性金属离子第一梯次缓慢释放,促进血管化、细胞生长增殖及成骨分化,与磷酸基结合的活性金属离子第二梯次缓慢释放,磷酸基为新骨形成提供优良的矿化微环境,活性金属离子的缓慢释放进一步延长了促进血管化 、细胞生长和成骨作用。因此煅烧骨、生物活性金属盐、羧基化-磷酸化壳聚糖三者协同作用,使本发明的骨修复材料具有优异的促进骨再生、骨修复作用,促进血管化、胶原蛋白再生和骨增量,缩短骨缺损修复时间,提高骨修复质量。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to a bone repair medical material, and more particularly to a chitosan derivative composite bone repair material, its preparation method and application, belonging to the field of biomedical materials. Background Technology
[0002] Bone defects of critical size caused by trauma, tumor resection, or congenital diseases that cannot heal spontaneously pose a global clinical challenge. Autologous bone transplantation is considered the "gold standard" for treating bone defects, but it suffers from problems such as donor shortages and the need for secondary surgeries. Allogeneic bone transplantation also faces risks such as donor shortages, immune rejection, and disease transmission. Therefore, developing biomaterials that can effectively promote the regeneration and repair of bone defects is an important regenerative medicine issue of concern to orthopedic surgeons and biomaterials researchers.
[0003] Human bone is mainly composed of two parts: inorganic and organic matter. The main component of the inorganic matter is hydroxyapatite, accounting for about 70%, while the main component of the organic matter is type I collagen, accounting for about 30%. Human bone hydroxyapatite exhibits a porous scaffold structure, supporting hematopoietic function, nutrient exchange, and serving as a pathway for blood vessels and nerves. Due to its similarity to human bone composition, hydroxyapatite possesses excellent biocompatibility and osteoconductivity, and has been widely used in bone repair. Compared to calcium phosphate-based chemicals, bio-derived hydroxyapatite, derived from calcined bone, has an excellent porous structure that is more similar to the porous structure of human bone. However, hydroxyapatite alone, lacking the organic matter component, cannot fully simulate the complex environment of the extracellular matrix (ECM) of bone cells, which involves cell adhesion, proliferation, and differentiation. This often leads to slow bone healing and poor healing outcomes. Therefore, it is essential to simultaneously construct both inorganic and organic components in bone repair materials.
[0004] Chitosan is a natural linear aminopolysaccharide polymer, insoluble in water and biodegradable. Its degradation product, glucosamine, is a direct precursor for the synthesis of glycosaminoglycans (key components of the extracellular matrix) in the human body. Chitosan derivatives possess excellent properties such as biocompatibility, biodegradability, and non-cytotoxicity, and have broad application prospects in biomedical materials. Carboxymethyl chitosan introduces carboxyl groups into the chitosan molecular chain, promoting wound healing. Since bone tissue is highly phosphorylated, phosphorylated polymers are considered biomimetic materials capable of reproducing key features of the natural bone microenvironment. Phosphorylated chitosan introduces phosphate groups into the chitosan molecular chain, endowing it with phosphate bioactive groups highly correlated with bone regeneration. Summary of the Invention
[0005] Based on the above background technology, the purpose of this invention is to provide a chitosan derivative composite bone repair material that can promote new bone formation and accelerate bone repair, as well as its preparation method and application.
[0006] This invention uses calcined bone with a porous structure as a scaffold, and combines it with metal ions and carboxylated-phosphorylated chitosan that promote bone regeneration, forming a composite structure of an active metal ion layer / carboxylated-phosphorylated chitosan layer / active metal ion layer, thereby preparing a chitosan derivative composite bone repair material. The porous structure of the calcined bone in this composite bone repair material better mimics the porous structure of natural bone. The bilayer composite active metal ions exhibit excellent angiogenesis and osteoproliferative activities. The composite macromolecular carboxylated-phosphorylated chitosan is an aminopolysaccharide polymer containing both carboxyl and phosphate groups. On the one hand, the carboxylated aminopolysaccharide better mimics the structure of extracellular matrix polysaccharides, which is beneficial for cell adhesion and growth. On the other hand, the phosphorylated aminopolysaccharide provides phosphate groups highly correlated with bone regeneration, forming an excellent microenvironment for bone regeneration. Furthermore, both carboxyl and phosphate groups can bind to active metal ions and be slowly released, further enhancing the bone regeneration and repair activities of the composite material.
[0007] A chitosan derivative composite bone repair material is characterized in that the composite bone repair material is composed of calcined bone, metal salt, and carboxylated-phosphorylated chitosan, wherein the mass ratio of calcined bone, metal salt, and carboxylated-phosphorylated chitosan is 100:(0.02-30):(0.1-50); the composite bone repair material has a multi-layer structure with calcined bone as the core framework, consisting of, from the inside out, a calcined bone layer, a metal salt layer, a carboxylated-phosphorylated chitosan layer, and a layer of carboxylated-phosphorylated chitosan combined with metal salt.
[0008] The composite bone repair material can be in the form of blocks, strips, columns, granules, flakes, or powder.
[0009] The calcined bone is calcined bone of different shapes from cattle, pigs, or other mammalian bones. Its main component is hydroxyapatite, and it has the porous structure of natural bone.
[0010] The metal salt is one or more of the divalent metal salts of calcium, magnesium, zinc, and strontium.
[0011] The carboxylated-phosphorylated chitosan is a chitosan molecule in which both phosphate and carboxyl groups are introduced. The molecular weight of the carboxylated-phosphorylated chitosan is greater than 10,000 Daltons, with a phosphate substitution degree of 20–85% and a carboxyl substitution degree of 10–100%. The phosphate substitution degree is defined as the molar percentage of phosphate groups to sugar units; the carboxyl substitution degree is defined as the molar percentage of carboxyl groups to sugar units.
[0012] The preparation method of the above-mentioned chitosan derivative composite bone repair material includes the following steps: (1) Preparation of calcined bone: Animal bones are calcined to obtain calcined bones of different shapes; (2) Preparation of carboxylated-phosphorylated chitosan: Weigh phosphorylated chitosan, stir to dissolve or disperse it in water, alcohol or alkaline solution to prepare phosphorylated chitosan aqueous solution or suspension; add carboxyl reagent, stir and react for 1 to 30 hours at room temperature to 70℃, neutralize the reaction system with alkaline solution to neutral after reaction; add ethanol to precipitate the reactants, centrifuge or filter, and then wash, dehydrate and dry to obtain carboxylated-phosphorylated chitosan.
[0013] The phosphorylated chitosan mentioned in step (2) above has a molecular weight greater than 10,000 Daltons and a phosphate substitution degree of 20-85% (molar percentage of phosphate to sugar unit); the carboxyl reagent is glyoxylic acid, propionic acid, or succinic anhydride, maleic anhydride, or chloroacetic acid, chloropropionic acid.
[0014] (3) Preparation of chitosan derivative composite bone repair material: 1) Weigh a metal salt, dissolve it in a solvent to obtain a metal salt solution, add the metal salt solution to calcined bone, stir to allow the metal salt solution to fully penetrate the porous structure of the calcined bone, and heat and dry the resulting solid-liquid mixture to obtain a calcined bone-metal salt composite; 2) Weigh a certain amount of carboxylated-phosphorylated chitosan, dissolve it in a solvent, add the carboxylated-phosphorylated chitosan solution to the dried calcined bone-metal salt composite to coat the calcined bone-metal salt composite, and heat and dry or freeze-dry the resulting solid-liquid mixture to obtain a calcined bone-metal salt-carboxylated-phosphorylated chitosan composite; 3) Weigh another metal salt, dissolve it in a solvent, add the metal salt solution to the calcined bone-metal salt-carboxylated-phosphorylated chitosan composite, stir, and heat and dry or freeze-dry the resulting solid-liquid mixture to obtain a calcined bone-metal salt-carboxylated-phosphorylated chitosan-metal salt composite, i.e., a chitosan derivative composite bone repair material.
[0015] In step (3) above, the metal salt is one or more of the divalent metal salts of calcium, magnesium, zinc and strontium, and the mass ratio of the divalent metal salts is (0.1-100):(0-20):(0-10):(0-5) for Ca:Mg:Zn:Sr; the solvent is water, methanol, ethanol, isopropanol or an aqueous solution of methanol, ethanol or isopropanol.
[0016] The chitosan derivative composite bone repair material of the present invention is used as a bone tissue filler in bone repair after fractures and bone defects to promote new bone formation, increase bone volume, accelerate bone repair, promote bone defect regeneration and healing, improve the repair quality of bone defects, and better meet the needs of bone repair.
[0017] The chitosan derivative composite bone repair material of the present invention is used as an alveolar bone filler in alveolar bone repair after tooth loss to promote new bone formation, increase bone volume, accelerate alveolar bone repair, and improve the quality of alveolar bone repair, thereby better meeting the needs of alveolar bone repair.
[0018] The chitosan derivative composite bone repair material of the present invention is used in plastic surgery as a filler for bone tissue, muscle or subcutaneous tissue to promote bone regeneration, promote collagen regeneration and deposition, accelerate new bone formation and increase bone mass, and can better meet the needs of medical aesthetic repair.
[0019] Technical effects of the present invention: (1) The calcined bone in the bone repair material of the present invention has natural bone hydroxyapatite components and a porous structure. Hydroxyapatite has osteoconductive and osteoinductive effects. The natural porous structure provides a stable three-dimensional support structure for new bone formation and also provides a storage pool for active metal salts. The divalent metal salts of calcium, magnesium, strontium, and zinc in the bone repair material are all metal salts necessary for bone growth and have the activity of promoting bone matrix mineralization and promoting bone regeneration. The carboxylated-phosphorylated chitosan in the bone repair material has phosphate groups and carboxyl groups that can be well bound to divalent metal salts. The binding force of phosphate groups to divalent metal ions is stronger, and the binding force of carboxyl groups to divalent metal salts is relatively stronger than that of phosphate groups. With a weak acid group, the large-molecule aminopolysaccharide backbone forms a series of active metal ions that release slowly through its phosphate and carboxyl groups, exhibiting varying binding and release forces. The aminopolysaccharide backbone better mimics the structure of extracellular matrix polysaccharides, promoting the growth and proliferation of bone marrow mesenchymal stem cells and osteoblasts. The first-stage slow release of active metal ions bound to the carboxyl groups promotes angiogenesis, cell growth and proliferation, and osteogenic differentiation. The second-stage slow release of active metal ions bound to the phosphate groups provides an excellent mineralization microenvironment for new bone formation. The slow release of active metal ions further prolongs the promotion of angiogenesis, cell growth, and osteogenic processes. Therefore, the synergistic effect of calcined bone, bioactive metal salts, and carboxylated-phosphorylated chitosan gives the bone repair material of this invention excellent bone regeneration and repair effects, promoting angiogenesis, collagen regeneration, and bone increase, shortening bone defect repair time, and improving bone repair quality.
[0020] (2) In the multi-layered structure formed from the inside out by calcined bone as the core, calcined bone, metal salt, carboxylated-phosphorylated chitosan, and the combination of carboxylated-phosphorylated chitosan and metal salt, the porous structure of calcined bone forms a storage pool for metal salt with bone regeneration-promoting activity. The carboxylated-phosphorylated chitosan coats the calcined bone-metal salt complex, forming an encapsulation layer for the metal salt. It also combines with the outermost divalent metal salt to form a carboxylated-phosphorylated chitosan metal salt with poor water solubility, which further enhances the encapsulation effect. This prolongs the degradation and absorption time of carboxylated-phosphorylated chitosan and forms a slow-release effect of different steps on the metal salt, prolonging the release time of active metal ions. Thus, the calcined bone, active metal salt, and carboxylated-phosphorylated chitosan are matched with each other, prolonging the time of bone repair material's effect of promoting bone regeneration and repair.
[0021] (3) The chitosan derivative composite bone repair material of the present invention uses carboxylated-phosphorylated chitosan with a molecular weight greater than 10,000 Daltons. The large molecular weight of carboxylated-phosphorylated chitosan binds more strongly to divalent metal salts than that of small molecules, and the degradation time is longer than that of small molecules, which can better match the bone repair process.
[0022] (4) The chitosan derivative composite bone repair material of the present invention has the functions of structural support, osteoinduction activity, collagen regeneration activity and osteogenic promotion. It has better effects on promoting bone regeneration, bone healing, bone increase and collagen regeneration. It can be used as a bone filler in bone defect repair, bone repair and bone increase to accelerate new bone formation, increase bone volume and promote bone defect repair. It can also be used as a filler for muscle and subcutaneous tissue to promote collagen regeneration, promote orderly deposition of collagen and increase the elasticity of skin and muscle tissue. Attached Figure Description
[0023] Figure 1 This is the XRD pattern of calcined bone.
[0024] Figure 2 This diagram illustrates the effects of different concentrations of carboxylated-phosphorylated chitosan on osteoblast proliferation.
[0025] Figure 3 This diagram illustrates the role of different concentrations of carboxylated-phosphorylated chitosan in promoting osteoblast mineralization.
[0026] Figure 4 This diagram illustrates the effect of different concentrations of carboxylated-phosphorylated chitosan on promoting the proliferation of L929 cells.
[0027] Figure 5 This is an anatomical diagram showing how composite bone repair materials promote skull repair in rats.
[0028] Figure 6 Masson staining image showing how composite bone repair materials promote the repair of skull defects in rats. Detailed Implementation
[0029] The present invention will be further described below with reference to the accompanying drawings and specific embodiments.
[0030] Example 1: Preparation of calcined bone Bovine cancellous bone was taken and cut into blocks of 1, 2, 3, 4, and 5 cm thickness, with no limit on length or width. After washing with water, the blocks were further processed into blocks and strips of different sizes: 0.5×0.5×0.5cm, 1×1×1cm, 1×1×5cm, and 2×2×3cm. Cylindrical blocks with a diameter of 0.2cm and a length of 0.5cm, and circular discs with a thickness of 0.2cm and a diameter of 0.5cm were also prepared. These were placed in a calcining furnace and calcined at 400, 800, and 1100℃ for 3, 5, and 5 hours respectively. After natural cooling, the blocks were washed with water and then naturally or heated to dry, yielding calcined bone blocks and discs of different sizes, exhibiting the porous structure of natural bone. The 1×1×1cm calcined bone was pulverized and sieved to obtain granules with a diameter of 0.5–3mm and powdered calcined bone after sieving. XRD analysis of the prepared calcined bone showed that its main component was hydroxyapatite (…). Figure 1 ).
[0031] In the preparation of calcined bone in Example 1, bovine bone, pig bone, or cancellous bone from other mammals can be used. The cancellous bone from bovine or pig bones is first cut into blocks, strips, cylinders, or flakes of different sizes, or crushed into particles and powder of different sizes, and then calcined at 400–1100°C for 3–20 hours. Alternatively, the bone blocks can be calcined at 400–1100°C for 3–20 hours first, and then cut, processed, and sieved as needed to obtain calcined bone in blocks, strips, cylinders, particles, flakes, or powder of different sizes. The main component of the prepared calcined bone is hydroxyapatite, which has the porous structure of natural bone.
[0032] Example 2: Preparation of carboxylated-phosphorylated chitosan 1 Weigh 60 g of NaOH, dissolve it in 300 ml of water with stirring to prepare a 20% (w / v) alkaline solution; weigh out phosphate groups with a degree of substitution of 38.5% and a molecular weight of 3.9 × 10⁻⁶. 410 g of phosphorylated chitosan was dissolved in an alkaline solution with stirring to prepare an alkaline aqueous solution of phosphorylated chitosan with a mass percentage of 3.3%. 40 g of chloroacetic acid was weighed and dissolved in 100 ml of water at a mass ratio of 1:4 (phosphorylated chitosan to carboxyl reagent 1 chloroacetic acid) to prepare a chloroacetic acid solution. The phosphorylated chitosan aqueous solution was stirred at 60 °C, and the chloroacetic acid solution was added dropwise. The reaction was stirred for 12 hours. After the reaction, the pH of the reaction system was adjusted to neutral with a 1 mol / L HCl aqueous solution. Ethanol was added to the reaction system to a concentration of 75%, the reactants were precipitated, filtered, and the solid and liquid were separated to obtain a solid. The solid was washed three times with a 75% ethanol aqueous solution, dehydrated with anhydrous ethanol, and dried by heating or vacuum drying to obtain carboxylated-phosphorylated chitosan 1. Elemental nitrogen analysis and acid-base titration analysis showed that its degree of carboxyl substitution was approximately 68.6%.
[0033] Example 3: Preparation of carboxylated-phosphorylated chitosan 2 Weigh out the phosphate group with a degree of substitution of 58.1% and a molecular weight of 3.2 × 10⁻⁶. 4 10 g of phosphorylated chitosan was dissolved in 400 ml of water to prepare a 2.5% (w / v) phosphorylated chitosan aqueous solution. 30 g of glyoxylic acid was weighed and added to the phosphorylated chitosan aqueous solution at a mass ratio of 1:3 (phosphorylated chitosan to carboxyl reagent 2-glyoxylic acid). The mixture was stirred and reacted at room temperature for 4 hours. After the reaction, the pH of the reaction system was adjusted to neutral using a 1 mol / L NaOH solution. Anhydrous ethanol was added to the reaction system to a concentration of 75%, precipitating the reactants. The precipitate was filtered, and the solid and liquid were separated to obtain a solid. The solid was washed three times with a 75% ethanol aqueous solution, dehydrated with anhydrous ethanol, and dried under vacuum at 60°C to obtain carboxylated-phosphorylated chitosan. Elemental nitrogen analysis and acid-base titration analysis showed that its carboxyl substitution degree was approximately 45%.
[0034] The phosphorylated chitosans in Examples 2 and 3 were purchased from Qingdao Boyite Biomaterials Co., Ltd. In the methods for preparing carboxylated-phosphorylated chitosan in Examples 2 and 3, the carboxyl reagent 1 can be chloroacetic acid, chloropropionic acid, or other carboxyl reagents that can participate in the reaction of Example 2; the carboxyl reagent 2 can be glyoxylic acid, propionic acid, or other carboxyl reagents that can participate in the reaction of Example 3; the molar ratio of phosphorylated chitosan to carboxyl reagent can be 1:0.3–10; Example 2 can also be reacted in an aqueous system of 0–70% ethanol or isopropanol, and Example 3 can also be reacted in an anhydrous system of ethanol, methanol, or isopropanol using succinic anhydride, maleic anhydride, etc., as carboxyl reagent 3. The prepared carboxylated-phosphorylated chitosan has a molecular weight greater than 10,000 Daltons, a phosphate substitution degree of 20–85% (molar percentage of phosphate to sugar unit), and a carboxyl substitution degree of 10–100% (molar percentage of carboxyl to sugar unit).
[0035] Example 4: Carboxylated-phosphorylated chitosan promotes osteoblast growth The carboxylated-phosphorylated chitosan prepared in Example 2 was irradiated and sterilized. Under aseptic conditions, carboxylated-phosphorylated chitosan culture media containing 125, 250, 500, and 1000 μg / mL of chitosan were prepared using α-MEM complete medium. A 1×10⁻⁶ μg / mL carboxylated-phosphorylated chitosan culture medium was then prepared. 4 MC3T3-E1 cells / mL were added to 96-well plates and cultured in a 5% CO2, 37°C cell culture incubator. After cell adhesion, the medium was replaced with α-MEM complete medium containing different concentrations of carboxylated-phosphorylated chitosan. A control group (0 μg / mL) was set up. Cells were cultured for 24 h and 48 h, and then subjected to live / dead cell staining, fluorescence microscopy, and MTT assay to detect absorbance at 492 nm. The relative cell proliferation rate (RGR) was calculated. Live / dead cell staining results are shown below. Figure 2 As shown, after 48 h of cell culture, the number of cells in each experimental group containing different concentrations of carboxylated-phosphorylated chitosan increased significantly. The cell proliferation rate of the 125 and 250 μg / mL concentration groups was significantly greater than that of the control group after 48 h, showing a significant difference (*). P <0.5,** P <0.01), indicating that carboxylated-phosphorylated chitosan promotes osteoblast growth and proliferation.
[0036] Example 5: Carboxylated-phosphorylated chitosan promotes osteoblast mineralization The concentration is 2×10 4 MC3T3-E1 cells per mL were cultured in 12-well plates in a 5% CO2, 37°C cell culture incubator. After cell adhesion, the medium was replaced with induction medium containing different concentrations of carboxylated-phosphorylated chitosan for further culture. At 14 and 21 days, alizarin red was used to stain the mineralized nodules formed by the cells. Results are as follows: Figure 3 As shown, after 14 days of culture, fewer mineralized nodules were produced by the cells, but the experimental group still had more calcified nodules than the control group. After 21 days of culture, the level of mineralized nodules in the experimental group containing 125 and 250 μg / mL carboxylated-phosphorylated chitosan was significantly increased, while the mineralized nodules in the control group (0 μg / mL) were smaller. This indicates that carboxylated-phosphorylated chitosan promotes osteoblast mineralization and is beneficial to bone regeneration.
[0037] Example 6: The effect of carboxylated-phosphorylated chitosan on promoting fibroblast proliferation Carboxylated-phosphorylated chitosan solutions with concentrations of 125, 250, 500, and 1000 μg / mL were used to study their effects on the proliferation of L929 fibroblast cells. L929 cells in the logarithmic growth phase were prepared into 1×10⁶ cells / mL groups. 4Cell suspensions at a concentration of [number] cells / mL were used in 96-well plates, with 200 μL of cell suspension added to each well. The plates were incubated in a 37°C cell culture incubator containing 5% CO2. After cell attachment, the culture medium was replaced with DMEM medium containing different concentrations of carboxylated-phosphorylated chitosan, with 200 μL added to each well. Cell growth morphology was observed under a light microscope at 24 h and 48 h. Simultaneously, cell viability / dead cell staining was performed, and images were taken under a fluorescence microscope. Results are as follows: Figure 4 As shown, different concentrations of carboxylated-phosphorylated chitosan all promoted the proliferation of L929 cells, indicating that it has the effect of promoting tissue healing.
[0038] Example 7: Preparation of chitosan derivative composite bone repair material 1) Weigh 20 g of the powdered calcined bone prepared in Example 1, weigh 2 g of calcium chloride and 0.5 g of magnesium chloride, dissolve the above metal salts in 62 ml of water to obtain a 4% metal salt solution (w / v). The mass-to-volume ratio of calcined bone to metal salt solution is 1:3.1. Add the metal salt solution to the calcined bone, stir and mix, and apply vacuum to ensure that the metal salt solution fully impregnates the porous structure of the calcined bone. Vacuum freeze-dry the resulting solid-liquid mixture to obtain the calcined bone-metal salt composite; 2) Weigh 4 g of the carboxylated-phosphorylated chitosan prepared in Example 2, add 80 Dissolve 1 g of calcium chloride in 75 ml of 20% ethanol aqueous solution to prepare a 5% carboxylated-phosphorylated chitosan solution (w / v). Add the carboxylated-phosphorylated chitosan solution to the dried calcined bone-metal salt composite at a mass-to-volume ratio of 1:4, so that the carboxylated-phosphorylated chitosan solution coats the calcined bone-metal salt composite. Heat and dry the resulting solid-liquid mixture to obtain the calcined bone-metal salt-carboxylated-phosphorylated chitosan composite. 3) Weigh 1 g of calcium chloride and dissolve it in 75 ml of 20% ethanol aqueous solution to prepare a 1.3% metal salt solution (w / v). Add the metal salt solution to the calcined bone-metal salt-carboxylated-phosphorylated chitosan composite at a mass-to-volume ratio of 1:3.8, stir, and heat and dry the resulting solid-liquid mixture to obtain the calcined bone-metal salt-carboxylated-phosphorylated chitosan-metal salt composite. This yields the powdered chitosan derivative composite bone repair material.
[0039] In Example 7, the calcined bone can be in different shapes such as blocks, strips, columns, granules, flakes, or powder; the total mass ratio of calcined bone, metal salt, and carboxylated-phosphorylated chitosan is 100:(0.02-30):(0.1-50); the metal salt is one or more of water-soluble calcium, magnesium, strontium, and zinc metal salts, and the mass ratio of the metal salt combination is Ca:Mg:Zn:Sr = (0.1-100):(0-20):(0-5):(0-5); the carboxylated-phosphorylated chitosan has a molecular weight greater than 10,000 Daltons, a phosphate substitution degree of 20-85%, and a carboxyl substitution degree of 10-100%; the mass of the metal salt weighed in preparation step 1) is the mass of the metal salt. The metal salt weighed in step 3) is 1 / 4 to 1 / 2 of the total mass, the concentration of the metal salt solution is 0.5 to 20% (w / v), and the volume-to-mass ratio of calcined bone to metal salt solution is 1:(0.1 to 5); the concentration of carboxylated-phosphorylated chitosan is 0.1 to 20% (w / v), and the volume-to-mass ratio of calcined bone to carboxylated-phosphorylated chitosan solution is 1:(0.1 to 5); the solvent is water or an aqueous ethanol solution with a concentration of 5 to 85% (v / v); the drying is heat drying or freeze drying; the chitosan derivative composite bone repair material is in blocks, strips, columns, granules, flakes or powder of different sizes.
[0040] Example 8: Effects of chitosan derivative composite bone repair material on the repair of skull defects and promotion of collagen regeneration in rats The powdered calcined bone prepared in Example 1 and the powdered chitosan derivative composite bone repair material prepared in Example 7 were respectively packaged into small glass bottles, 1g per bottle, 5 bottles of each type, and sterilized by irradiation for later use. Fifteen male SD rats were randomly divided into a blank control group, a calcined bone group, and a composite bone material group. The observation period was 90 days post-surgery. After anesthesia, the rats' heads were shaved and the skin disinfected. Under sterile conditions, a 2.0 cm incision was made along the right side of the midline from the occipital bone to the frontal bone, fully exposing the right parietal bone, occipital bone, and part of the frontal bone. A 5 mm diameter hollow drill was used to vertically drill the exposed skull, forming a 5 mm diameter circular skull defect. The corresponding materials were then placed into the skull defect according to the group. The blank control group was not filled with material, the calcined bone group was filled with powdered calcined bone, and the composite bone material group was filled with powdered chitosan derivative composite bone repair material. After filling, the incision was sutured open, and the skin was disinfected. The experimental rats were injected with 40,000 units of penicillin post-surgery and fed normally.
[0041] The mice were sacrificed 90 days post-surgery, and the skull repair results were observed through autopsy. Figure 5As shown in the figure, the blank control group still showed a large unclosed area of the skull at the defect site; in the calcined bone group, the calcined bone material was fixed to the skull defect site by connective tissue, the boundary between the calcined bone and the defective skull was relatively clear, and bone healing was slow; in the composite bone material group, the bone repair material was tightly fixed to the skull defect site by connective tissue, the new bone tissue extended along the defect edge towards the defect center, the boundary between the bone repair material and the defect site was blurred, and most of the skull defect site had healed. Anatomical observation results indicate that the chitosan derivative composite bone repair material of this invention significantly promotes bone tissue regeneration, accelerates bone defect healing, shortens the healing cycle, and improves the quality of bone repair.
[0042] Ninety days post-surgery, anatomical skull fragments were harvested, and the marginal area of the repaired defect was taken. The fragments were fixed in formaldehyde solution, decalcified with EDTA decalcification solution, paraffin-embedded, sectioned, and stained with Masson stain to observe the in vivo collagen regeneration induced by the material. Masson staining results are shown below. Figure 6 As shown, Masson staining stains collagen fibers blue. At 90 days post-surgery, the blue collagen at the edge of the skull defect repair in the blank group was the thinnest, indicating low collagen fiber production. In the calcined bone group, cavities formed after decalcification of the implanted calcined bone material were visible, with blue collagen fibers entering the gaps between the calcined bone materials. However, the amount of collagen fiber production was insufficient, resulting in a lighter blue color. In the composite material group, cavities formed after decalcification of the implanted bone material were also visible, but the number of cavities was less than in the calcined bone group, and the amount of blue collagen fiber production was greater, resulting in a deeper and denser blue color. This indicates that the composite bone repair material has the effect of inducing and promoting collagen regeneration and orderly deposition.
[0043] Therefore, chitosan derivative composite bone repair materials can be used as plastic surgery materials in orthopedics, for filling bone tissue, muscle and subcutaneous tissue, to promote bone regeneration, collagen regeneration, orderly collagen deposition, accelerate new bone formation and increase bone mass.
[0044] The carboxylated-phosphorylated chitosan described in this invention is an aminopolysaccharide polymer that simultaneously possesses phosphate and carboxyl groups. It better mimics the structure and microenvironment of extracellular matrix aminopolysaccharides, and promotes the proliferation, mineralization, and osteogenic differentiation of bone marrow mesenchymal stem cells and osteoblasts, as well as bone tissue regeneration, collagen regeneration, and deposition.
[0045] The above-described embodiments are merely preferred embodiments of the present invention and therefore should not be construed as limiting the scope of protection of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention.
Claims
1. A chitosan derivative composite bone repair material, characterized in that, The composite bone repair material is composed of calcined bone, metal salt, and carboxylated-phosphorylated chitosan, with a mass ratio of 100:(0.02-30):(0.1-50). The composite bone repair material has a multi-layered structure with calcined bone as the core framework, consisting of, from the inside out, a calcined bone layer, a metal salt layer, a carboxylated-phosphorylated chitosan layer, and a layer of carboxylated-phosphorylated chitosan combined with metal salt.
2. The chitosan derivative composite bone repair material as described in claim 1, characterized in that, The carboxylated-phosphorylated chitosan is a chitosan molecule in which phosphate groups and carboxyl groups are introduced simultaneously. The molecular weight is greater than 10,000 Daltons, the degree of phosphate substitution is 20-85%, and the degree of carboxyl substitution is 10-100%.
3. The chitosan derivative composite bone repair material as described in claim 1, characterized in that, The calcined bone is calcined bone from cattle, pigs, or other mammalian bones.
4. The chitosan derivative composite bone repair material as described in claim 1, characterized in that, The composite bone repair material is in the form of blocks, strips, columns, granules, flakes, or powder.
5. The chitosan derivative composite bone repair material as described in claim 1, characterized in that, The metal salt is one or more of the divalent metal salts of calcium, magnesium, zinc, and strontium.
6. A method for preparing a chitosan derivative composite bone repair material according to any one of claims 1-5, characterized in that, Includes the following steps: (1) Preparation of calcined bone: Animal bones are calcined to obtain calcined bones of different shapes; (2) Preparation of carboxylated-phosphorylated chitosan: Weigh phosphorylated chitosan, stir to dissolve or disperse it in water, alcohol or alkaline solution to prepare phosphorylated chitosan aqueous solution or suspension; add carboxyl reagent, stir and react for 1 to 30 hours at room temperature to 70℃, neutralize the reaction system with alkaline solution to neutral after reaction; add ethanol to precipitate the reactants, centrifuge or filter, and then wash, dehydrate and dry to obtain carboxylated-phosphorylated chitosan; (3) Preparation of chitosan derivative composite bone repair material: 1) Weigh a metal salt, dissolve it in a solvent to obtain a metal salt solution, add the metal salt solution to calcined bone, stir to allow the metal salt solution to fully penetrate the porous structure of the calcined bone, and heat and dry the resulting solid-liquid mixture to obtain a calcined bone-metal salt composite; 2) Weigh a certain amount of carboxylated-phosphorylated chitosan, dissolve it in a solvent, add the carboxylated-phosphorylated chitosan solution to the dried calcined bone-metal salt composite to coat the calcined bone-metal salt composite, and heat and dry or freeze-dry the resulting solid-liquid mixture to obtain a calcined bone-metal salt-carboxylated-phosphorylated chitosan composite; 3) Weigh another metal salt, dissolve it in a solvent, add the metal salt solution to the calcined bone-metal salt-carboxylated-phosphorylated chitosan composite, stir, and heat and dry or freeze-dry the resulting solid-liquid mixture to obtain a calcined bone-metal salt-carboxylated-phosphorylated chitosan-metal salt composite, i.e., a chitosan derivative composite bone repair material.
7. The preparation method of the chitosan derivative composite bone repair material as described in claim 6, characterized in that, The carboxyl reagent is one of chloroacetic acid, chloropropionic acid, glyoxylic acid, propionic acid, succinic anhydride, and maleic anhydride.
8. The preparation method of the chitosan derivative composite bone repair material as described in claim 6, characterized in that, The metal salt is one or more of the divalent metal salts of calcium, magnesium, zinc and strontium, and the mass composition ratio of the divalent metal salt combination is (0.1~100):(0~20):(0~10):(0~5).
9. The application of the chitosan derivative composite bone repair material according to any one of claims 1-5 as a bone tissue filler in the bone repair of fractures, bone defects, and alveolar bone.
10. The chitosan derivative composite bone repair material according to any one of claims 1-5, used in orthopedic surgery as a filler for bone tissue, muscle or subcutaneous tissue.